Pemilihan Kepala Daerah dan Wakil Kepala Daerah Secara Langsung dalam Perspektif Demokrasi Lokal - Patrisia Yubiliana Herti Mbu; Saryono Yohanes; Umbu Lily Pekuwali (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
The regional head election system is a long political journey decorated with the trappings of political elite interests and public will, central and regional interests. This research is a normative legal study, using a conceptual approach with literature study or document study techniques. The legal materials were processed through several processes, which were then analyzed qualitatively and normatively. The results of this study indicate: first, the direct election system in selecting Regional Heads and Deputy Regional Heads as a manifestation of people's sovereignty, increasing accountability, creating legitimate leaders, strengthening local democracy, providing wider choices to the community. Second, ideally the direct election system for Regional Heads and Deputy Regional Heads can be achieved with steps, namely quality elections that include high community participation in voting, honest and fair processes, intelligent voters; quality regional head candidates that include competence and integrity, clear vision and mission, inclusive representation; accountability and transparency that include effective supervision, budget and policy transparency; supporting conditions that include a strong legal framework, independent organizing institutions, a mature democratic culture; and recognition of local values.